Communicative sensitivity in palliative care: a case on the "Happiness Angels" of Rajbala Foundation. Issue 2 (3rd June 2017) - Shukla, Sangeeta; Sinha, Saloni
Abstract : Subject area: The subject areas are business communication, human resource management and health care. Study level/applicability: The case was designed for use in a first-year MBA-level course in business communication but would serve well in a course for executives or for advanced undergraduates. It might also be assigned in general management courses to evoke discussion on communication skills required in sensitive and critical situations; human resource courses; and course on health care. Case overview: Palliative care is a specialized medical care focussing on improving the quality of life of patients suffering from life-threatening illnesses. It addresses symptom management and psychosocial and spiritual concerns of the patient and its caregivers. With the intent to alleviate the sufferings of terminally ill patients, Rajbala Foundation, a non-government organization (NGO), works at the psychosocial and spiritual levels. While training their volunteers in effective palliative care communication, it often encounters challenges such as socio-cultural variations, organizational challenges, appropriate verbal and nonverbal communication, etc. This teaching case focuses on the communication challenges faced by the volunteers of Rajbala Foundation. It would lead to a broader discussion on communicating empathically during critical situations. The case has a focus on NGOs, and non-profit organizations, public sector management, health-care management and human resources management. There is significant literature on communication skills for medical practitioners in palliative care. As an increasing number of NGOs step in to provide the second level of care to critically ill patients in non-physical domains, there is a need to understand the role of effective communication for such care providers. This case deals with non-medical care providers in palliative care; the issues of communication they face as they interact with patients; and the skills they require to address the emotional and spiritual needs of patients and their families. Expected learning outcomes: The aim of this case is to raise awareness of the complexities involved in the communication process during an emotional and sensitive interaction. It aims to encourage volunteers involved in palliative care to reflect on good communication practices when communicating with patients and family members. After reading this case, the students should be able to discuss the complexities involved in the communication process when communicating in situations with high emotional involvement; understand the core elements of emotional interactions for effective practice; and emphasize the need for the development of communication skills within palliative care. Supplementary materials: Teaching Notes are available for educators only. Please contact your library to gain login details or email support@emeraldinsight.com to request teaching notes. Subject code: CSS 6: Human Resource Management